Reclaiming justice for energy-vulnerable populations: Evidence from the city of los angeles - Dong Xie; Senhong Cai; Xuechen Gui (Energy Strategy Reviews, 2024)
The issues of energy accessibility and vulnerability have garnered significant attention in recent research. However, previous studies have tended to emphasize access-based energy justice while neglecting vulnerability-based energy justice, particularly in emergency scenarios. This study aims to address this gap by examining the conceptual differences between the two concepts through practical examples and exploring the profile of energy-vulnerable individuals. In this study, a dataset comprising 1650 buildings in Los Angeles was selected. A spatial regression model was employed to investigate the factors influencing energy use intensity (EUI) in the years 2019 and 2020, as well as the rate of change in EUI between these two years. This analysis was conducted within the framework of the two-tier model of energy justice combining energy accessibility and vulnerability proposed in this article. The results revealed that, considering the impact of the COVID-19 pandemic on the urban energy environment, more demographic types experienced adverse effects, indicating energy-vulnerable populations. Among these groups, older adults were impacted adversely most, followed by the Asian population and the unemployed population. The two-tier framework of energy justice proposed in this article compensates for the shortcomings of traditional energy justice perspectives and confirms the typology of energy-vulnerable populations more objectively. The findings also confirm the spatial dependence and heterogeneity of these impacts. The findings will prompt a reevaluation of energy equity in urban settings and offer a theoretical foundation for energy policy decision-making.